Trap Engineering Against The Effectiveness of Caught Imago Rhinoceros Beetle on Palm Oil Plants - Darmadi Erwin Harahap; Siti Hardianti Wahyuni; Muhammad Darwis; Mukhlis; Amir Mahmud (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to find out the engineering of traps against the effectiveness of caught by rhinoceros beetles on palm oil plants. This research was carried out on farmers who were planted in Sidadi Village, Batang Angkola Subdistrict, South Tapanuli Regency. From October to December 2020. The method used in this study is a survey with a sampling technique that is purposive sampling. Traps are installed at as many as 2 points on an area of 720 m2 with a population of 110 palm oil stalks. Traps were placed at the location of many O. rhinoceros attacks. Ember has a trap size of 20 liters, and at the base of the bucket made 4 holes diameter of 2 mm for water disposal. The zinc plate is cleaved in 2 parts of the faucet 30 x 25 cm arranged in pairs in a 4-room-shaped space placed on top of the bucket and tied with a fastening wire. Pheromones are removed from the packaging and hung on zinc traps given gaps on 4 sides. Trap II, Plastic bucket as a trap. The plastic bucket size of 20 liters, the lid of the bucket is perforated with as many as 5 holes (diameter 55 mm) placed upside down, based on the plastic bucket made 4 holes (diameter 2 mm) for water disposal; Pheromones (Ethyl 4-mathyloctanoate) are removed from the packaging, wrapped around a small 10 cm long wire, and attached to the lid of a plastic bucket that is placed upside down. The results showed that the most effective trap installation is trap 1 which has a higher ability to control rhinoceros beetle pests (Oryctes rhinoceros) which are as many as 46 tails compared to 2 traps with as many as 41 tails on plants that have not produced palm oil